Beyond the Sum of its Parts : Combining Financial Instruments for Impact and Efficiency - Hosier, Richard; Kulichenko, Nataliya; Maheshwari, Aditi; Toba, Natsuko; Wang, Xiaodong (World Bank, Washington, DC, 2014)
The Global Environment Facility (GEF), carbon finance, and the Clean Technology Fund (CTF) constitute the bulk of dedicated funding for low-carbon development. To achieve the largest possible impact, practitioners must learn to combine these resources in the same project or program in order to both reduce transaction costs and maximize synergies. This issues brief considers six projects that are using resources from one or all of these sources in combination with development finance to advance low-carbon development. It lays out a conceptual basis for how GEF, carbon finance, and CTF resources can be fit together to make a wider range of mitigation projects financially and economically attractive.